Finite element analysis of a geodesic dome structure by using staadpro software - Mohamad Aidil, Abd Kassim (2015)
Finite element analysis (FEA) has become common place in recent years, and is now widely used in the construction industry during analysis and design of a structure. Numerical solutions to very complicated stress problems can now be obtained routinely using FEA. Dome structure is unique due to the ability to withstand a larger span with minimum interference. Geodesic domes are efficient structure because it consists of triangular element along the hemisphere to resist the load. Triangle element is the most effective shape in truss and the combination between triangle element and dome make geodesic dome a strong structure to resist load. STAAD.Pro software is based on the finite element analysis and this software widely used in industry because it accuracy during analysis a structure by using finite element method (FEM). This study is about analysis the structural behaviour of the Geodesic Dome Structure by using STAAD.Pro Software to determine the maximum deflection and all the reaction force on the structure when the load is applied to the model.